2018
DOI: 10.1002/tal.1579
|View full text |Cite
|
Sign up to set email alerts
|

Optimal vertical configuration of combined energy dissipation outriggers

Abstract: The damped outrigger system emerged as an improvement of the conventional outriggers with the aim to provide supplemental damping and to contribute to the vibration control in super tall buildings where this system is usually applied. In addition to viscous dampers (VDs), buckling-restrained braces (BRBs) have also been employed as energy dissipating members in outriggers. Nevertheless, the combined use of outriggers with VDs and BRBs in the same structure has not yet been studied. Such combination can contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…28 A more elaborated case study can be found in Lu et al 29 Subsequently, the 3D finite element analysis of such system equipped with viscous dampers or/and BRB were examined in Refs. 3032. These studies further paved the way for applying damped outriggers in engineering practice.…”
Section: Introductionmentioning
confidence: 86%
“…28 A more elaborated case study can be found in Lu et al 29 Subsequently, the 3D finite element analysis of such system equipped with viscous dampers or/and BRB were examined in Refs. 3032. These studies further paved the way for applying damped outriggers in engineering practice.…”
Section: Introductionmentioning
confidence: 86%
“…An 8.1‐m‐tall, reduced‐scale damped‐outrigger specimen utilizing BRB and viscous dampers was tested by shaking table experiments. [ 20 ] The test results suggested that when the specimen is equally divided into nine segments, the damped‐outriggers with BRB and viscous damper can be located at the seventh and the fifth segments from the ground, which is the optimal damped‐outrigger configuration to minimize the seismic response. The test results have also been verified by finite element analysis results.…”
Section: Introductionmentioning
confidence: 99%
“…R. J. Smith and Willford [7] proposed the concept of the damped-outrigger by inserting dampers between the outrigger truss end and the perimeter column to increase the damping, instead of increasing the stiffness. [8], [9], [10], [11], [12] investigated The efficiency of damped outrigger systems, [13], [14], [15] investigated damped-outrigger system incorporating buckling restrained braces. Virtual outriggers was proposed by R. Shankar Nair [16] and also called belt-truss system.…”
Section: Introductionmentioning
confidence: 99%